2009
DOI: 10.1177/1350508409337582
|View full text |Cite
|
Sign up to set email alerts
|

Domination in Organizational Fields: It’s Just Not Cricket

Abstract: This article demonstrates how deep engagement with Bourdieu’s theory of the field enriches scholarly understanding of institutional processes. A historical narrative of institutional formation and change in firstclass County cricket in England as a field of restricted cultural production is presented. The narrative illustrates how focusing attention on the position of agents within the field, the relations of production within the field, and the social context, which includes social class, provides a path for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 109 publications
(115 reference statements)
0
33
0
4
Order By: Relevance
“…Battilana, 2006;Wright, 2009). Attempts to transcend this have primarily involved the knitting or grounding of wider social theoretical perspectives with institutional theory--structuration theory (Barley and Tolbert, 1997;Scott, 2008); critical realism (Leca and Naccache, 2006) and Bourdieusian theory (Battilana, 2006;Wright, 2009). Yet, despite this, we contend, that these approaches fail to adequately theorize the empirical phenomena to which they relate.…”
Section: A Figurational Critique Of Institutional Theorymentioning
confidence: 97%
See 1 more Smart Citation
“…Battilana, 2006;Wright, 2009). Attempts to transcend this have primarily involved the knitting or grounding of wider social theoretical perspectives with institutional theory--structuration theory (Barley and Tolbert, 1997;Scott, 2008); critical realism (Leca and Naccache, 2006) and Bourdieusian theory (Battilana, 2006;Wright, 2009). Yet, despite this, we contend, that these approaches fail to adequately theorize the empirical phenomena to which they relate.…”
Section: A Figurational Critique Of Institutional Theorymentioning
confidence: 97%
“…Bourdieu's (1990) concept of field-a version of which has been subsumed by institutional approaches to organizational studies-has been specifically identified and advocated as a means to overcome the structure-agency dilemma within institutional theory (e.g. Battilana, 2006;Wright, 2009). However, we argue that even here institutional theorists continue to sustain the dualism of structure-agency.…”
Section: A Figurational Critique Of Institutional Theorymentioning
confidence: 99%
“…French sociologist, Pierre Bourdieu, regarded as one of the most influential figures of the twentieth century (Yang, 2014) develops a framework to account for the dynamics of power in society -how power is transferred and social order maintained within and across generations -which integrate a theory of social structures (field), a theory of power relations (forms of capital), and a theory of the individual (habitus) (Dobbin, 2008;Stringfellow et al, 2015). His theories have been applied by studies seeking to adopt processual or practice based perspectives and account for dynamics of social change (Kitchin and Howe, 2014;Wright, 2009;Grenfell and James, 2004).…”
Section: Bourdieu's System Of Thoughtmentioning
confidence: 99%
“…Second, the paper adds to discussions about connecting new institutional theory with Bourdieu's theory of practice. While there are some approaches to connect new institutionalism with Bourdieu's concepts of field and capital (see, e.g., Battilana (2006); Lounsbury and Ventresca (2003); Oakes, Townley, and Cooper (1998); Wright (2009)), there are few that introduce the concept of habitus in institutional research. I argue that combining Bourdieu's habitus concept with new institutional theory might foster the theory's development, particularly at the micro-level, because of the unique insights Bourdieu's theory might add to institutional processes.…”
Section: Implications For New Institutional Theorymentioning
confidence: 99%